Estimating retention benchmarks for salvage logging to protect biodiversity - Simon Thorn (Nature Portfolio, 2020)
Salvage logging has become a common practice to gain economic returns from naturally disturbed forests, but it could have considerable negative effects on biodiversity. Here the authors use a recently developed statistical method to estimate that ca. 75% of the naturally disturbed forest should be left unlogged to maintain 90% of the species unique to the area.